Coronary artery anomalies presenting with ST-segment elevation myocardial infarction - Jlenia Marchesini; Gianluca Campo; Riccardo Righi; Giorgio Benea; Roberto Ferrari (Clinics and Practice, 2011)
ST-segment elevation MI (STEMI) is a rare presentation in patients with coronary artery anomalies. In these patients, the identification of the culprit lesion and its treatment may be difficult, particularly in the emergency setting of primary percutaneous coronary intervention (PCI). From January 2008 to April 2011, 1015 STEMI patients received coronary artery angiography and primary PCI in our centre. Of these, 5 (0.4%) patients showed a coronary artery anomaly. In this paper we reported two rare cases: i) the first is a single coronary artery originating from right sinus of Valsalva; ii) the second is a separate origin of 3 coronary arteries originating from the right sinus of Valsalva. In conclusion, coronary artery anomalies presenting with STEMI are really uncommon, but often are a challenge. The integration between traditional coronary artery angiography and multidetector computerized tomography is crucial to optimize the interventional and medical management of these patients